A STUDY OF INFLUENCE OF VERTICAL VIBRATION ON HEAT TRANSFER COEFFICIENT FROM HORIZONTAL CYLINDERS (Journal of Engineering, 2008)
Electrically heated horizontal cylinders of diameters 2.15cm,3cm, and 3.8cm were vibrated vertically in stagnant air at a frequency (10,15,20Hz) and amplitude range from (0.0005m) to (.0076m). The effect of different parameters on the heat transfer ratio (hv/ho) was investigated from its outer surface. It is concluded that, heat transfer ratio increases at high frequency and small diameter. Vibration Reynolds number has good effects on heat transfer ratio. (Gr.Pr) has bad indication on heat transfer ratio at high temperature difference (high heat flow). The vibration intensity also has good influence on heat transfer.